Modeling the spatial distribution of the striped dolphin (Stenella coeruleoalba) and common bottlenose dolphin (Tursiops truncatus) in the Gulf of Taranto (Northern Ionian Sea, Central-eastern Mediterranean Sea). (October 2016) - Carlucci, Roberto; Fanizza, Carmelo; Cipriano, Giulia; Paoli, Chiara; Russo, Tommaso; Vassallo, Paolo
Highlights: GAM and RF models were applied for predicting the habitat preference of S. coeruleoalba and T. truncatus . Main variables affecting the spatial distribution of both species were identified. RF revealed the highest accuracy and precision. Abstract: Although the EU Marine Strategy Framework Directive (MSFD) is largely based on the establishment of environmental targets and associated proxies to achieve Good Environmental Status (GES), a full suite of ecological indicators for all the ecosystem components is not currently available for ongoing assessment and regular update of GES targets. This is because effective indicators and management actions aimed at preserving/rebuilding marine biodiversity should be found from the knowledge of the spatial distribution of target species and extension of critical habitats as well as their overlapping with human activities, pressure and impacts. In this regard, the spatial distributions of the striped dolphin Stenella coeruleoalba and the common bottlenose dolphin Tursiops truncatus in the Gulf of Taranto (Northern Ionian Sea, Central-eastern Mediterranean Sea) were investigated by means of a generalized additive model (GAM) and a Random Forest (RF) based on sighting data collected during standardized vessel-based surveys carried out from 2009 to 2015. Eight predictive variables were considered, taking into account both the local physiographic features and human activities existing in the investigated area, suggesting an innovative approach to habitat modeling. In particular, the explanatory variables depth, distance from industrial areas and distance from the coast proved to significantly influence the distribution of both dolphin species. In addition, the distribution of S. coeruleoalba and T. truncatus were also significantly shaped by the distance from the navy exercise areas and the fishing areas, respectively. On the contrary, the slope and the distance from the main commercial routes never provided any significant influence. The reliability of GAM and RF models in predicting the spatial distribution of both dolphins was tested by applying the Youden Index method to the ROC curves. The RF model allowed the projection of the expected presence/absence pattern of S. coeruleoalba and T. truncatu s to produce the preference habitat versus non habitat map. In particular, the RF model predicted that the striped dolphin is widely present in the central and deeper part of the Gulf of Taranto. In contrast, the common bottlenose dolphin seems to be mainly distributed along the coasts in both the eastern and western sector of the basin. A clear overlapping of the preference habitats estimated for S. coeruleoalba and T. truncatus is shown north of Punta Alice and in front of Policoro as well as offshore from Ugento in the eastern and western parts of the investigated area, respectively. Finally, the critical habitats of S. coeruleoalba and T. truncatus are the outcome of both the influence of environmental conditions and anthropogenic pressures presently occurring in the Gulf of Taranto, basically indicating the need for conservation measures, especially considering that the area is expected to be considered for hydrocarbon prospecting. These results contribute to setting up a baseline reference for future assessment of environmental marine disturbances using cetaceans, which are considered a key group in the MSFD, as an ecological indicator.